Alpha-L-Fucosidase Has Diagnostic Value in Prostate Cancer With “Gray-Zone PSA” and Inhibits Cancer Progression via Regulating Glycosylation - Zhang, Cong; Liu, Jikai; Chao, Fan; Wang, Shiyu; Li, Dawei; Han, Dunsheng; Xu, Zhonghua; Xu, Guoxiong; Chen, Gang (Frontiers in Oncology, 2021)
1) Background: To explore the diagnostic value of Alpha-L-fucosidase (AFU) in prostate cancer (PCa) with “gray-zone PSA” and to investigate the correlation between AFU expression and clinicopathological characteristics of PCa patients. 2) Methods: The level of AFU and other necessary clinicopathological variables of patients were retrieved from electronic medical records. The transcriptome profiling and clinical information of PCa patients were obtained from Cancer Genome Atlas (TCGA) database. The protein level of AFU in tissue was assessed by immunohistochemistry (IHC). All the data were processed by appropriate analysis methods. The p-value of <0.05 was considered statistically significant. 3) Results: AFU showed ideal diagnostic value for PCa with PSA levels ranging from 4 to 10 ng/mL, and its optimal cutoffs were 19.5 U/L. Beyond this, low AFU expression was associated with high pathological grade, T stage and N stage, more postoperative residual tumors, poor primary therapy outcome as well as shorter progress-free interval. KEGG analysis illustrated FUCA1/FUCA2 exerted the tumor-suppressive function by regulating the glycosylation. 4) Conclusions: AFU(<19.5 U/L) could effectively distinguish the PCa from the patients with “gray zone PSA” and low expression of AFU was an independent unfavorable predictor for the clinicopathological characteristics of PCa patients.